ABRAHAM MASLOW'S THEORY AND ITS IMPLEMENTATION IN ISLAMIC RELIGIOUS EDUCATION - Munif, Emi Bahrul; Prehanto; Nurul Aziz; Mun'amah, Anatun Nisa (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
This research aims to: 1) discuss the theories of Abraham Maslow 2) this research also discusses the implementation of Abraham Maslow's theory in Islamic religious education. This research is classified as library research. Researchers in this case conduct research using incidental means as the main instrument and analyze scientific literature in the form of journal articles, books, scientific magazines and other scientific publications related to the discussion on the theme proposed by him. The results of this study indicate that: 1) Abraham Maslow argues that humans live to fulfill their lives or needs. Needs in human life are triggered in several levels. Starting from basic needs to the highest needs. Based on Maslow's belief, the greater the value of the need to be achieved, the more serious the individual is to get it. needs that start from the most basic things include: Physiological needs, security needs, a sense of belonging and love, self-esteem, self-actualization. 2) While the Implementation of Abraham Maslow's Theory in Islamic Religious Education a teacher as a student facilitator before starting learning makes an initial plan or design. Related to methods; Providing reinforcement for something good done by students, teachers should interact well with students through small attention so that students feel